Popularization of high yielding varieties of wheat (Triticum aestivum L.) in Jhalawar district of Rajasthan state through Frontline Demonstrations - Verma, Arjun Kumar; Jeengar, Kishan Lal; Ram, Jeeva; Naager, Khem Chand (Journal of Cereal Research, 2016)
Total 487 Frontline demonstrations (FLDs) at farmers field were laid out on wheat (Triticum aestivum L.) to demonstrate production potential and economic benefits of improved practices (IP) comprising high yielding varieties namely Raj-3765 and Raj-4037 in Jhalawar district of humid zone V of Rajasthan state during rabi seasons from 2007-08 to 2010-11 in irrigated farming situation. The percent increased yield under improved practices ranged from 07.81 to 21.85 (Raj-4037)and 14.52 (Raj-3765) in respective years. The average extension gap, technology gap and technology index were 5.29 qha-1, 10.14 qha-1 and 21.51 percent, respectively in different varieties of wheat. The improved practices gave higher benefit cost ratio ranging from 1.20 to 1.98 with a mean of 1.53 compared to farmers practices (1.25). The productivity of wheat per unit area could be increased by adopting feasible scientific and sustainable management practices with a suitable variety. Considering the above facts, Frontline demonstrations werecarried out in a systematic and scientific manner on farmer’s field to show the worth of a new variety and convincing farming community about potentialities of improved production management technologies of wheat for further adoption.